2013
DOI: 10.3109/01676830.2013.788674
|View full text |Cite
|
Sign up to set email alerts
|

Results of Combined Multispecialty Endoscopic Dacryocystorhinostomy

Abstract: While a joint approach to eDCR did not appear to significantly improve efficacy, it offered the advantage of having an otolaryngologist assess and treat concurrent sinonasal pathology, which was seen in every patient in our series. Given our findings, as well as the technical difficulty often associated with the procedure, there may be great utility in performing eDCR in conjunction with an otolaryngologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…12 No adjunctive procedures such as septoplasty or polypectomy were performed on any of our patients. In our opinion, if such procedures are deemed necessary they should only be performed by an otolaryngologist, as recommended by Kim et al 14 While some studies have demonstrated that such procedures improve success rates of END-DCR by improving access to the surgical site, 15 we have not found access to be difficult with decongestion of the lateral wall of the nose, after reflection and removal of the nasal mucosa.…”
Section: Discussionmentioning
confidence: 64%
“…12 No adjunctive procedures such as septoplasty or polypectomy were performed on any of our patients. In our opinion, if such procedures are deemed necessary they should only be performed by an otolaryngologist, as recommended by Kim et al 14 While some studies have demonstrated that such procedures improve success rates of END-DCR by improving access to the surgical site, 15 we have not found access to be difficult with decongestion of the lateral wall of the nose, after reflection and removal of the nasal mucosa.…”
Section: Discussionmentioning
confidence: 64%